2014
DOI: 10.5799/ahinjs.01.2014.02.0397
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in the diagnosis of acute appendicitis

Abstract: Objective: Patients who is presented to ED with the complaint of abdominal pain account an important number in the ED practice. Availability of rapid and inexpensive tests is crucial in the differential diagnosis of these patients. Hemogram parameters is one of them. In this study, we investigated the biomarkers in hemogram parameters of the patients diagnosed with acute appendicitis.Methods: Data of 520 patients who were operated with the presumed diagnosis of appendicitis in our hospital between 01/01/2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…The mean age of the patients included in our study did not differ statistically between the groups. In accordance with the studies in the literature, male sex was dominant in the acute appendicitis group and male/female ratio was similar in the negative appendectomy group (9,13,17) . The negative appendectomy rate was 19.7% in female patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean age of the patients included in our study did not differ statistically between the groups. In accordance with the studies in the literature, male sex was dominant in the acute appendicitis group and male/female ratio was similar in the negative appendectomy group (9,13,17) . The negative appendectomy rate was 19.7% in female patients.…”
Section: Discussionsupporting
confidence: 91%
“…In studies investigating the diagnostic value of NLR, for negative appendectomy was reported to be between 12.9-18.5% (8,9,13,17,21) .In our series, this rate was found to be 17.1%.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation